EMPOWERING TEACHERS FOR SUSTAINABLE DEVELOPMENT GOALS: KEY DRIVERS OF TRANSFORMATIVE EDUCATION - Rahmawati, Emma; Husna, Mujlauwidzatul; Irvana, Wahyu (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The importance of education in achieving sustainable development goals (SDGs) has increased in today's evolving world. To achieve these goals, education must transform beyond traditional approaches and empower learners to create change. Teachers play a crucial role in driving this transformative education and ensuring its successful implementation. This research uses the literature research method. This method was chosen to understand new phenomena that are developing through studying various sources and remains reliable in answering research questions. The analysis was carried out using the content analysis method. By teaching teachers the necessary knowledge, skills, and support, we can prepare a generation of learners who can contribute actively to reaching the SDGs. Teachers using curriculum integration, pedagogical innovation, community engagement, and technology can motivate and empower their students to become agents of change and promote sustainable development. Educational institutions, policymakers, and communities must work together to establish an appropriate environment that values and empowers teachers transformative education.